Assessment of Metered-Dose Inhalers with Spacer Technique among Postgraduate Trainees - Tahir Iqbal; Qaisar Iqbal; Bahar Ali; Raza Ullah; Shahida Naz; Haleema (Gandhara University, 2023)
OBJECTIVES Most obstructive airway disease medications are used via inhalers, and their proper use is significant for effectively treating these diseases. Most patients misuse it. However, some studies showed that many physicians also do not know the proper meter dose inhaler with the spacer technique. This study aimed to assess metered-dose inhalers with spacer technique among postgraduate trainee doctors. METHODOLOGY This cross-sectional study was carried out in the Khyber Teaching Hospital Peshawar. The total time was six months, from Dec 6 2020, to Jun 5 2021. Postgraduate trainee (PGT) doctors of either gender with an age range of 25 to 35 years were included in the study from different departments. Those with every use of inhalers were excluded from the study. Demographic details of PGTs, like age and gender, were recorded. RESULTS Among 96 patients, males were 85 (88.54%), and females were 11 (11.46%). The mean age was 30.02±1.84 years, and the mean training experience was 2.0521 ±0.89. Inhaler technique was Proper in 20 (20.83%), Improper in 51 (53.13%) and Poor in 25 (26.04%) doctors. Those with more training periods, pulmonology rotation, attended workshops on inhaler techniques and with relatives using inhalers were more acknowledged of proper meter dose inhalers (MDIs) with spacer technique. CONCLUSION Only one-fifth of the postgraduate trainees know proper MDIs techniques. The attendance of workshops and pulmonology rotation is encouraged to enhance the knowledge of physicians regarding MDIs techniques.